PENGARUH PROFITABILITAS, LEVERAGE, PERTUMBUHAN PERUSAHAAN, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Liliy Chynthiawati; Jonnardi Jonnardi (Jurnal Paradigma Akuntansi, 2022)
This research was conducted with the aim of knowing the effect of profitability, leverage, company growth, and liquidity on firm value in infrastructure, transportation and utility sector companies listed on the Indonesia Stock Exchange in 2015-2019. This study usedpurposive sampling as a technique in determining the sample and the data obtained were35. The data processing technique uses multiple regression analysis with the help of the Eviews11 SV application. The test results show that profitability and company growth have a positive and significant effect on firm value, while leverage and liquidity have a negative and significant effect on firm value in infrastructure, transportation and utility sector companies listed on the Indonesia Stock Exchange in 2015-2019. The implication of this research is that the company must pay attention to the leverage and liquidity ratio so that it is not too high because it can affect firm value.